Implementasi Prinsip Syariah dalam Pengelolaan UMKM Kuliner (Studi Kasus Cafe Hiray Kota Parepare) - Sri Indah Wahyuni; Sri Shifwa Surastri; Nurfadillah Ramadhani Yusuf; Nurul Hikmah; Rezki Fani (Jurnal Bersama Ilmu Ekonomi (EKONOM), 2026)
This study aims to analyze the sharia business management practices of the Hiray Cafe MSME operating in Parepare City. Hiray Cafe is known as a popular cafe among various groups due to its affordable prices, good product quality, and aesthetic and comfortable atmosphere. This study highlights the application of sharia principles through the provision of halal food and beverage products, the use of ingredients in accordance with Islamic law, and attention to employee religious aspects such as maintaining discipline in performing the five daily prayers. Hiray's business structure includes a division of roles from the owner, manager, HRD, to operational divisions such as baristas, pastry, kitchen, and waiters, which helps work effectiveness and coordination at the MSME scale. The marketing management system utilizes social media such as Instagram, TikTok, WhatsApp, and collaboration with courier partners to expand digital market reach. In addition, a business culture that emphasizes product quality, personalized service, halal certification, and a comfortable atmosphere are key values in business management. The analysis shows that Hiray Cafe has consistently implemented elements of Sharia business management, particularly in halal certification, service ethics, and honest and professional relationships with customers and partners. These findings can serve as a reference for other MSMEs in developing relevant and competitive Sharia-based business models in the digital era.